The marigold (Calendula officinalis L.) drug essential oil agents change under different fertilization settings in small plot trial - Lelesz, Judit; Nagy, Éva; Csajbók, József (Acta Agraria Debreceniensis, 2016)
During our research we investigated the marigold's (Calendula officinalis L.) nutrient requirements with different fertilization setting in small-plot trial. We measured SPME (Solid phase microextraction) and GC-MS (gas chromatograph-mass spectrometer) we examined the effects of the different fertilization settings for the herb's main active ingredients of essential oil's percentage.Based on the results, it was concluded, the essential oil agents' percentage breakdowns significantly depending on the cropping technologies. Besides that it is possible, based on Pearson's correlation test the marigold essential oil agents relationship can also be a major factor.